PENGARUH KUALITAS KEHIDUPAN KERJA, BEBAN KERJA DAN PEMBERDAYAAN TERHADAP KINERJA KARYAWAN PT. APPAREL ONE INDONESIA 1 SEMARANG - Iriana Rahma Nugrahani; Bambang Suko Priyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study deals with how the influence of the quality of work life, workload and empowerment on the performance of employees of PT. Apparel One Indonesia 1 Semarang. The purpose of the study: to determine the effect of the quality of work life, workload and empowerment on employee performance partially and simultaneously. This research was conducted on 105 employees who were used as research samples through a questionnaire with the research method using multiple linear regression analysis. The results of the study: there is negative and insignificant effect on the quality of work life on employee performance partially, there is a negative and insignificant effect on workload partially on employee performance, there is a positive and significant influence on empowerment partially on employee performance, there is a significant effect on quality of life work, workload and empowerment of employee performance simultaneously.